MULTIMODAL RADIATION DIAGNOSIS OF BREAST CANCER - Мадумарова Зарнигор Шухрат кизи; Хафизова Руфина Радиковна; Нишанова Ю.Х.; Ходжамова Г.А.; Хусанбаева Д.Д.; Ахмадова М.А (Galaxy International Interdisciplinary Research Journal, 2023)
To date, one of the topical issues of modern oncology is the problem of breast cancer (BC), which ranks first in the structure of evilneoplasms in women. Every year, more than 1.5 million new cases of breast cancer are detected in the world, while more than 50% of women die from this pathology. According to the literature, the process of "rejuvenation" of breast cancer over the past decades has seen an increase in this disease among women at a younger age under 40 years [1]. In addition, breast cancer in young women may have a worse prognosis and more aggressive biological behavior than breast cancer in elderly patientsapprox. Previous studies have shown that in young women, breast cancer is diagnosed at a later stage, characterized by high proliferative activity, low differentiated Oh, with estrogen receptor negative tumors, with the presence of asular invasion lymphs [7; 10]. Previously, the definition of "young women" included patients under 35 years of age, since 2012, the World Health Organization has developed a new age classification [12], according to which: persons under the age of 44 are young; 45-59 years old - to mature; 60-74 years old to the elderly; 75-90 years old - to the elderly. The threshold of longevity is considered to be the achievement of 90 years or more.